Direct evidence of plant-pathogenic activity of fungal metabolites of Trichothecium roseum on apple - Zabka, Martin; Drastichová, Kamila; Jegorov, Alexandr; Soukupová, Julie; Nedbal, Ladislav (Mycopathologia, 2006)
Apples were exposed to various concentrations of roseotoxins - metabolites of Trichothecium roseum and kinetic fluorescence imaging was used to detect the area influenced by the phytotoxin. Contrast was quantified within these images between the areas exposed to roseotoxins and the untreated areas. It was proved that roseotoxin B is able to penetrate apple peel and produce chlorotic lesions. Activity of roseotoxin B is similar as the activity of destruxins, host specific phytotoxins of Alternaria brassicae parasitic on canola.
Keywords: Fluorometry; Plant Diseases; mitosporické houby; depsipeptidy; Depsipeptides; Mitosporic Fungi; Malus; fluorometrie; nemoci rostlin